2014
DOI: 10.2139/ssrn.2464018
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stability and Financial Inclusion

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
89
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 15 publications
17
89
3
2
Order By: Relevance
“…Similarly the greater the number of SME borrowers, the lower the probability of default which indicates more financial stability as we found significant positive effects of SMEBTB on financial stability. Our results are consistent with the findings of (Han & Melecky 2013;Hannig & Jansen 2010;Morgan & Pontines 2014;Okpara 2011). Thus, we argue that broader access to and use of finance for SMEs lead to significantly improve resilience of the overall financial system and thus financial stability.…”
Section: Estimated Results With the Baseline Modelsupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly the greater the number of SME borrowers, the lower the probability of default which indicates more financial stability as we found significant positive effects of SMEBTB on financial stability. Our results are consistent with the findings of (Han & Melecky 2013;Hannig & Jansen 2010;Morgan & Pontines 2014;Okpara 2011). Thus, we argue that broader access to and use of finance for SMEs lead to significantly improve resilience of the overall financial system and thus financial stability.…”
Section: Estimated Results With the Baseline Modelsupporting
confidence: 93%
“…Among control variables, similar to the findings of Morgan and Pontines (2014), we found significant positive impacts of GDP per capita on Z-score; that is countries with higher income are less likely to be financially instable. We also found that uses of more percentage of liquid assets to deposits and short term funding leads to more financial stability.…”
Section: Estimated Results With the Baseline Modelsupporting
confidence: 82%
See 3 more Smart Citations